"Playthings of the Brain": Phantom Visions in Charles Bonnet Syndrome. Issue 5 (4th July 2019) - Strong, Joe
ABSTRACT: Charles Bonnet Syndrome (CBS) is a condition of the visually impaired, in which hallucinations – or, more appropriately, visions – of geometric patterns, people, and objects appear within the visual field. Most people with CBS are older adults, a function of increased likelihood of visual deterioration in later life, but the condition can occur at any age. Diagnostic criteria vary among professions, but generally includes awareness that the visions are not real, the absence of other accompanying sensory hallucinations, and the absence of dementia or other neurological condition. The mechanism by which the phenomenon occurs is not well understood, although some speculation exists that it is akin to phantom limb syndrome. Although there has recently been increasing awareness about the condition, many in the fields of medicine, optometry, and social work have not heard of it. As front-line providers for clients, it is important that social workers be well informed about the condition to alleviate anxiety our clients may have about expressing their experiences with the condition.